EBV-specific T-cell immunity: relevance for multiple sclerosis - Behrens, Malina; Comabella, Manuel; Lünemann, Jan D. (Frontiers in Immunology, 2024)
Genetic and environmental factors jointly determine the susceptibility to develop multiple sclerosis (MS). Improvements in the design of epidemiological studies have helped to identify consistent environmental risk associations such as the increased susceptibility for MS following Epstein–Barr virus (EBV) infection, while biological mechanisms that drive the association between EBV and MS remain incompletely understood. An increased and broadened repertoire of antibody and T-cell immune responses to EBV-encoded antigens, especially to the dominant CD4+ T-cell EBV nuclear antigen 1 (EBNA1), is consistently observed in patients with MS, indicating that protective EBV-specific immune responses are deregulated in MS and potentially contribute to disease development. Exploitation of B-cell trajectories by EBV infection might promote survival of autoreactive B-cell species and proinflammatory B:T-cell interactions. In this review article, we illustrate evidence for a causal role of EBV infection in MS, discuss how EBV-targeting adaptive immune responses potentially modulate disease susceptibility and progression, and provide future perspectives on how novel model systems could be utilized to better define the role of EBV and viral pathogens in MS. Insights gained from these studies might facilitate the development of prevention strategies and more effective treatments for MS.